Development and clinical validation of passive shoulder exoskeleton with novel gravity compensation mechanism for stabilizing arm tremor of surgeons during minimally invasive surgery - Choi, Ho Seon; Lee, Seung Jun; In, Hyunki (Frontiers in Bioengineering and Biotechnology, 2024)
IntroductionDuring tasks like minimally invasive surgery (MIS), various factors can make working environment not be ergonomic, and those situations will accumulate fatigue in the surgeon's muscles which will inevitably lead to poor surgical performance. Therefore, there has been a need for technical solutions to solve this problem and one of the methods is exoskeleton robots.MethodsWe designed a passive shoulder exoskeleton whose workspace could be used for MIS to assist the surgeon's movements and performed computational and clinical validation. First, the joint order of the shoulder exoskeleton, which consists of three degrees of freedom, was configured differently from previous studies so that the singularity can be located outside the workspace. And a novel gravity compensation mechanism was developed to replace the existing one, which could no longer be used due to these changes on order of joints. Afterwards, it was computationally verified using statics and kinematics whether sufficient shoulder muscle assistance could be implemented for the entire developed system. Lastly, we manufactured an apparatus that simulated the surgical environment in which the shoulder exoskeleton robot would actually be used, recruited human participants, and conducted an experiment.ResultsThrough computational validation, we can guess that the developed shoulder exoskeleton can provide 18.14% reduction of muscle activation to the wearers in workspace. And the results of clinical experiments with human subjects show that activation of deltoid posterior, medial and anterior decreased with average −8.33%, −14.55%, and −21.0%, respectively during MIS-simulated tasks with developed shoulder exoskeleton than without it. And arm tremor which is equals to movement variability also decreased with average 9.85% by using shoulder exoskeleton and maximum −19.5% in a certain position.DiscussionThese experimental results show that our shoulder exoskeleton and its novel gravity compensation mechanism has enough clinical effectiveness for workers of underhead tasks, especially surgeons who conduct MIS. It reduced deltoid activations of wearers and also stabilized arm tremor which are directly related to performance of fine manipulative task, so that this research implies that shoulder exoskeletons are also need for underhead tasks and our shoulder exoskeleton has possibility to contribute to those utilities.